Makna dan Tradisi Pukul Manyapu di Negeri Morella Kecamatan Leihitu Kabupaten Maluku Tengah - Renwarin, Nurhayati (Lembaga Intelektual Muda Maluku, 2024)
The land of Morella is one of the customary lands found in the Leihitu Peninsula. In this Morella Country, a traditional ceremony has taken place that has been carried out for generations known as